Contemporary Culinary Innovation (Rawon Using Shellfish Ingredients) - Eddy Roesdiono; Izza Addin Perdana Putra (Cerdika: Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the use of mussels as a basic ingredient in rawon culinary innovation and its impact on taste and consumer appeal. The research method used is a quantitative approach with data collection through a structured questionnaire. The results showed that the majority of respondents considered mussel-based rawon as a unique innovation and provided a new culinary experience. However, there are several obstacles that affect the level of consumer acceptance, such as the taste that does not match expectations, the texture of mussels is different from beef, and the price is considered more expensive. The main challenge in developing mussel rawon is the adaptation of people's tastes who are accustomed to meat-based rawon and the perception of the texture of mussels. However, the opportunity to develop mussel rawon is quite large, especially as an alternative to healthier and more environmentally friendly food. To increase its appeal, further research is needed to explore processing techniques that can improve the taste and texture of mussels, as well as a broader market analysis to understand consumer preferences in depth. In addition, economic studies related to the supply chain and production cost efficiency are also important factors in the development of this innovation.